Functionalized crown ethers for lithium ion batteries
By adding functionalized crown ether to the electrolyte of lithium-ion battery, the cathode stability problem of lithium-ion batteries under high voltage and high temperature conditions is solved, and the stable cycle and performance improvement of the battery is achieved.
Patent Information
- Application Number
- CN202380056662.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-25
- Filing Date
- 2023-07-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-07-25
AI Technical Summary
Existing lithium-ion batteries have cathode stability problems under high voltage and high temperature conditions, resulting in electrochemical oxidation of materials, gas generation and interface resistance, affecting the cycle life and performance of the battery.
Functionalized crown ether is used as an additive for electrolytes. By coordinating with metal ions, the intercalation and deintercalation of lithium ions are improved, forming a stable cathode electrolyte interface (CEI), improving high-temperature performance and storage stability.
The stable circulation of lithium-ion batteries under high voltage and high temperature conditions is achieved, which extends the cycle life of the battery and improves the high-temperature performance and storage stability of the battery.
Smart Images

Figure CN119605011A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of the filing date of U.S. Provisional Patent Application No. 63 / 392,025, filed on July 25, 2022, the entire contents of which are incorporated herein by reference. Technical Field
[0003] The present disclosure relates to functionalized crown ethers that can be used to reduce battery resistance, increase cycle life, and improve high-temperature performance; an electrolyte containing the functionalized crown ethers; and an electrochemical energy storage device using the electrolyte. Background Art
[0004] Lithium-ion batteries are used extensively in consumer electronics, electric vehicles (EVs), and energy storage systems (ESS) and smart grids. Recently, lithium-ion batteries with voltages above 4.35 V have gained importance due to higher capacity and subsequent energy density benefits. However, the stability of cathode (or positive electrode) materials at these potentials decreases due to increased oxidation. This may lead to electrochemical oxidation of the materials to produce gases, which may degrade the performance of the battery. The cathode active materials that are capable of intercalating / deintercalating lithium ions may dissolve in the non-aqueous electrolyte, resulting in structural damage to the materials and will lead to increased interfacial resistance. These lithium-ion batteries are also typically exposed to extreme temperatures during their operation. The SEI (solid electrolyte interface) layer formed on the anode (or negative electrode) gradually decomposes at high temperatures, resulting in more irreversible reactions and causing capacity loss. Similarly, the CEI (cathode electrolyte interface) also loses stability at high temperatures. These reactions occur at both the positive and negative electrodes during cycling, but are generally more severe at higher temperatures due to faster kinetics. Next-generation lithium-ion batteries for consumer electronics, EVs, and ESSs will require significant improvements in electrolyte components relative to current state-of-the-art lithium-ion batteries.
[0005] Shuttle of positive and negative ions between battery electrodes is the primary role of the electrolyte. Historically, researchers have focused on developing battery electrodes, while electrolyte development has been limited. Conventional lithium-ion batteries use carbonate-based electrolytes with large electrochemical windows that can transport lithium ions. These electrolytes require functional additives for passivating the anode and forming a stable SEI, as well as additives for stabilizing the cathode. At the same time, additives that allow high-voltage, high-energy lithium-ion batteries to cycle stably and safely need to be designed and developed.
[0006] As the industry moves to higher energy cathode materials for higher energy batteries, stable, efficient and safe cycling of the battery in a wide voltage window is necessary. By adding different co-solvents and additives, lithium-ion battery electrolytes can be tuned based on their application. This tunability enables the development of different additives for high voltage stability and safety of lithium-ion batteries.
[0007] Crown ethers have been reported in the literature as additives that can coordinate with metal ions, which can have a wide range of beneficial effects such as improving lithium solvation, reducing charge transfer resistance, and removing dissolved manganese ions from the cathode (Ochida, M.; Doi, T.; Domi, Y.; Tsubouchi, S.; Nakagawa, H.; Yamanaka, T.; Abe, T.; Ogumi, ZJ Electrochem. Soc. 2013, 160, A410, Xu, K. Chem. Rev. 2004, 104, 4303). Japanese patent JP2000195548A has reported the use of crown ethers and aza crown ethers as components of lithium secondary battery electrolytes. U.S. Patent No. 9,130,231 reported the use of crown ethers as components in microporous membranes of lithium ion batteries. Chinese patent CN103613576 reported the synthesis of macrocyclic cyclic sulfates.
[0008] In this paper, functionalized crown ethers are reported as additives for lithium-ion batteries. When added to the electrolyte, these molecules allow for the stabilization of the cathode and the overall electrolyte system. Batteries containing such additives in the electrolyte will enable safe, long cycle life, and high energy lithium-ion batteries. Therefore, the incorporation of these new additives is needed to improve the performance of lithium-ion batteries. Summary of the invention
[0009] According to one aspect of the present disclosure, a new type of compound and an electrolyte for an electrochemical energy storage device are provided. The electrolyte comprises: a functionalized crown ether; an aprotic organic solvent; and a metal salt.
[0010] According to another aspect of the present disclosure, an electrolyte for an electrochemical energy storage device is provided, the electrolyte comprising: a functionalized crown ether; an aprotic organic solvent; a metal salt; and at least one additive.
[0011] According to another aspect of the present disclosure, an electrochemical energy storage device is provided, comprising: a cathode; an anode; a separator and an electrolyte, wherein the electrolyte comprises a functionalized crown ether, an aprotic organic solvent and a metal salt.
[0012] According to another aspect of the present disclosure, an electrolyte for an electrochemical energy storage device is provided, the electrolyte comprising: a functionalized crown ether; an aprotic organic solvent; a metal salt; and at least one additive; wherein the aprotic organic solvent comprises an open-chain or cyclic carbonate, a carboxylate, a nitrite, an ether, a sulfone, a sulfoxide, a ketone, a lactone, a dioxolane, a glycol dimethyl ether, a crown ether, a siloxane, a phosphate, a phosphite, a monophosphazene or a polyphosphazene or a mixture thereof.
[0013] According to another aspect of the present disclosure, an electrolyte for an electrochemical energy storage device is provided, the electrolyte comprising: a functionalized crown ether; an aprotic organic solvent; a metal salt; and at least one additive; wherein the cation of the metal salt is aluminum, magnesium, or an alkali metal such as lithium or sodium.
[0014] According to another aspect of the present disclosure, an electrolyte for an electrochemical energy storage device is provided, the electrolyte comprising: a functionalized crown ether; an aprotic organic solvent; a metal salt; and at least one additive; wherein the additive comprises a compound containing at least one unsaturated carbon-carbon bond, a carboxylic anhydride, a sulfur-containing compound, a phosphorus-containing compound, a boron-containing compound, a silicon-containing compound or a mixture thereof.
[0015] These and other aspects of the present disclosure will become apparent upon review of the following detailed description and appended claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Differential capacity curves of battery formation showing dQ / dV curves for electrolytes tested in NMC622 / Gr cells;
[0017] Figure 2 The room temperature cycle life characteristics in the cycle life diagram of the electrolyte tested in the NMC622 / Gr battery are shown;
[0018] Figure 3 Differential capacity curves of cell formation showing dQ / dV curves for electrolytes tested in NMC811 / SiO+Gr cells; and
[0019] Figure 4 The room temperature cycle life characteristics in the cycle life diagram of the electrolyte tested in NMC811 / SiO+Gr cells are shown. DETAILED DESCRIPTION
[0020] The disclosed technology generally relates to lithium ion (Li-ion) battery electrolytes. In particular, the present disclosure relates to functionalized crown ethers containing at least one oxygen-phosphorus bond or at least one oxygen-sulfur bond; electrolytes containing these functionalized crown ether materials; and electrochemical energy storage devices containing these electrolytes.
[0021] The present disclosure describes a lithium-ion battery electrolyte having an electrolyte formulation that can overcome cathode stability challenges in lithium-ion batteries, particularly those lithium-ion batteries that include cathode materials with high nickel content at high voltages. Current state-of-the-art lithium-ion batteries include cathode materials that have low nickel content and operate at high voltages, or cathode materials that have high nickel content but operate at low voltages. State-of-the-art electrolytes are tuned for these situations, and researchers have recently begun to focus on using new electrolyte formulations to achieve high nickel, high voltage battery cathodes. There is a need to develop an electrolyte solution for cycling lithium-ion batteries with high voltage, high nickel cathodes. The present technology is based on innovative functionalized crown ethers that, when incorporated into electrolytes, can improve the stability of high voltage, high energy cathodes. When used at low weight loadings, electrolyte ethers form a unique cathode electrolyte interface (CEI) and do not over-passivate the cathode. In addition, the improved CEI improves high temperature performance and storage stability, and has no effect at room temperature.
[0022] In an embodiment, the electrochemical energy storage device electrolyte includes a) an aprotic organic solvent; b) a metal salt; c) a functionalized crown ether compound material. In an embodiment, the functionalized crown ether compound material is present in a concentration of 0.01 wt % to 10 wt % of the electrolyte.
[0023] In aspects of the present disclosure, at least one functionalized crown ether organic compound according to formula I, II or III has a molecular structure of
[0024]
[0025] in:
[0026] n is an integer ranging from 1 to 8;
[0027] X is independently oxygen or sulfur; and
[0028] R is independently further bonded to C1-C 12 Substituted or unsubstituted alkyl group or C6-C 14 halogen, oxygen or sulfur atom of an aryl group,
[0029] Any hydrogen atom may be replaced by an epoxide, halogen, alkyl, alkoxy, perfluoroalkyl, silane, silaneoxy, silane, sulfoxide, amide, azo, ether and thioether group or a combination thereof, or the carbon atom may be unsubstituted or may be substituted by an epoxide, halogen, alkyl, alkoxy, perfluoroalkyl, silane, silaneoxy, silane, sulfoxide, amide, azo, ether and thioether group or a combination thereof.
[0030] Specific examples of molecules according to the present disclosure are as listed below:
[0031]
[0032]
[0033] These examples are merely illustrative and are not intended to limit the disclosure of the appended claims.
[0034] The addition of functionalized crown ethers to lithium-ion battery systems allows for chelation of metal ions and stabilization of the cathode surface. The resulting effect inhibits further oxidative decomposition of the remaining electrolyte components, which would otherwise occur upon contact with the cathode material. The inclusion of a phosphorus-oxygen bond ensures good coordination with high-nickel, high-energy cathode materials.
[0035] The present disclosure also includes methods for synthesizing functionalized crown ethers, and the use of such molecules in lithium-ion battery electrolytes. These molecules impart greater stability to electrolytes and cathodes operating at higher potentials.
[0036] In aspects of the present disclosure, the electrolyte includes a metal salt. In an embodiment, the metal salt is present in the electrolyte in a range of 10 wt % to 30 wt %. In an embodiment, the cation of the metal salt is aluminum, magnesium, or an alkali metal such as lithium or sodium. A variety of lithium salts can be used, including, for example, Li(AsF6); Li(PF6); Li(CF3CO2); Li(C2F5CO2); Li(CF3SO3); Li[N(CP3SO2)2]; Li[C(CF3SO2)3]; Li[N(SO2C2F5)2]; Li(ClO4); Li(BF4); Li(PO2F2); Li[PF2(C2O4)2]; Li[PF4C2O4]; alkyl lithium fluorophosphates; Li[B(C2O4)2]; Li[BF2C2O4]; Li2[B 12 Z 12-j H j ];Li2[B 10 X 10-j’ H j’ or a mixture of any two or more thereof, wherein Z is independently halogen at each occurrence, j is an integer from 0 to 12 and j' is an integer from 1 to 10.
[0037] In aspects of the present disclosure, the electrolyte includes an aprotic organic solvent selected from open chain or cyclic carbonates, carboxylates, nitrites, ethers, sulfones, sulfoxides, ketones, lactones, dioxolanes, glycol dimethyl ethers, crown ethers, siloxanes, phosphates, phosphites, monophosphazenes or polyphosphazenes or mixtures thereof. In embodiments, the solvent is present in the electrolyte in a range of 50 wt % to 90 wt %.
[0038] Examples of aprotic solvents for producing electrolytes include, but are not limited to, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, dipropyl carbonate, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, bis(trifluoroethyl) carbonate, bis(pentafluoropropyl) carbonate, methyl trifluoroethyl carbonate, methyl pentafluoroethyl carbonate, methyl heptafluoropropyl carbonate, methyl perfluorobutyl carbonate, ethyl trifluoroethyl carbonate, ethyl pentafluoroethyl carbonate, ethyl heptafluoropropyl carbonate, ethyl carbonate perfluorobutyl ester, fluorinated oligomers, methyl propionate, ethyl propionate, butyl propionate, dimethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol, dimethyl ether, polyethylene glycol, triphenyl phosphate, tributyl phosphate, hexafluorocyclotriphosphazene, 2-ethoxy-2,4,4,6,6-pentafluoro-1,3,5,2-5,4-5,6-5 triazatriphosphine, triphenyl phosphite, cyclopentane, dimethyl sulfoxide, methyl ethyl sulfone, ethyl vinyl sulfone, allyl methyl sulfone, divinyl sulfone, fluorophenyl methyl sulfone and γ-butyrolactone.
[0039] In aspects of the present disclosure, the electrolyte further includes at least one additive to protect the electrode and the electrolyte from degradation. Therefore, the electrolyte of the present technology may include an additive that is reduced or polymerized on the electrode surface to form a passivation film on the electrode surface.
[0040] In an embodiment, the additive is a substituted or unsubstituted straight chain, branched or cyclic hydrocarbon comprising at least one oxygen atom and at least one aryl, alkenyl or alkynyl group. The passivation film formed by such an additive may also be formed by a substituted aryl compound or a substituted or unsubstituted heteroaryl compound, wherein the additive comprises at least one oxygen atom.
[0041] Representative additives include glyoxal bis(diallyl acetal), tetra(ethylene glycol) divinyl ether, 1,3,5-triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasiloxane, 2,4,6-triallyloxy-1,3,5-triazine, 1,3,5-triacryloylhexahydro-1,3,5-triazine, 1,2-divinyl furoate (1,2-divinyl furoate), 1,3-butadienyl carbonate, 1-vinylazetidin-2-one, 1-vinylaziridine-2-one, 1-vinylpiperidin-2-one, 1-vinylpyrrolidin-2-one, 2,4-divinyl-1,3-dioxane, 2-amino-3-vinylcyclohexanone, 2-amino-3-vinylcyclopropanone, 2-amino-4-vinylcyclobutanone, 2-amino-5-vinylcyclopentanone, 2-aryloxy-cyclopropanone, 2-vinyl-[1,2]oxazetidine, 2-vinylaminocyclohexanol, 2-vinylaminocyclopropanone, 2-vinyloxetane, 2-vinyloxy-cyclopropanone, 3-(N- 3-vinylamino) cyclohexanone, 3,5-divinyl furoate, 3-vinyl azetidin-2-one, 3-vinyl aziridine-2-one, 3-vinyl cyclobutanone, 3-vinyl cyclopentanone, 3-vinyl oxaziridine, 3-vinyl oxetane, 3-vinyl pyrrolidone-2-one, 2-vinyl-1,3-dioxolane, acrolein diethyl acetal, acrolein dimethyl acetal, 4,4-divinyl-3-dioxolane-2-one, 4-vinyl tetrahydropyran, 5-vinyl piperidine-3-one, allyl glycidyl ether, butadiene monoxide, butyl vinyl ether, dihydropyran-3-one, divinyl butyl carbonate (divinyl divinyl carbonate, divinyl crotonate, divinyl ether, divinyl carbonate, divinyl silicate, divinyl sulfate, divinyl sulfite, divinyl methoxypyrazine, divinyl methyl phosphate, divinyl propylene carbonate, ethyl phosphate, methoxy-o-terphenyl, methyl phosphate, oxetane-2-yl-vinylamine, oxiranyl vinylamine, vinyl carbonate, vinyl crotonate, vinyl cyclopentanone, vinyl ethyl-2-furoate, vinyl ethylene carbonate, vinyl silicate, vinyl sulfate, vinyl sulfite, vinyl methacrylate, vinyl phosphate, vinyl-2-furoate, vinyl cyclopropanone, vinyl oxirane, β-vinyl-γ-butyrolactone, or a mixture of any two or more thereof.In some embodiments, the additive can be a cyclotriphosphazene substituted with F, an alkoxy group, an alkenyloxy group, an aryloxy group, a methoxy group, an allyloxy group, a sulfonic acid group, or a combination thereof. For example, the additive can be a (divinyl)-(methoxy) (trifluoro) cyclotriphosphazene, (trivinyl) (difluoro) (methoxy) cyclotriphosphazene, (vinyl) (methoxy) (tetrafluoro) cyclotriphosphazene, (aryloxy) (tetrafluoro) (methoxy) cyclotriphosphazene, (methylsulfonyl) cyclotriphosphazene, or a (diaryloxy) (trifluoro) (methoxy) cyclotriphosphazene compound or a mixture of two or more such compounds.
[0042] In some embodiments, additive is sulfur-containing compound, phosphorus-containing compound, boron-containing compound, silicon-containing compound, fluorine-containing compound, nitrogen-containing compound, compound containing at least one unsaturated carbon-carbon bond, carboxylic anhydride or its mixture. In some embodiments, additive is a mixture of ethylene carbonate, vinyl ethylene carbonate or any two or more such compounds. In addition, additive exists with the scope of 0.01 weight % to 10 weight %.
[0043] In some embodiments, the additive is a completely or partially halogenated phosphate compound, an ionic liquid, or a mixture thereof. The halogenated phosphate may include 4-fluorophenyl diphenyl phosphate, 3,5-difluorophenyl diphenyl phosphate, 4-chlorophenyl diphenyl phosphate, trifluorophenyl phosphate, heptafluorobutyl diphenyl phosphate, trifluoroethyl diphenyl phosphate, bis(trifluoroethyl)phenyl phosphate, and bis(trifluoroethyl)phenyl phosphate. The ionic liquid may include tris(N-ethyl-N-methylpyrrolidinium)thiophosphate bis(trifluoromethylsulfonyl)imide, tris(N-ethyl-N-methylpyrrolidinium)phosphate bis(trifluoromethylsulfonyl)imide, tris(N-ethyl-N-methylpiperidinium)thiophosphate bis(trifluoromethylsulfonyl)imide, tris(N-ethyl-N-methylpiperidinium)phosphate bis(trifluoromethylsulfonyl)imide, N-methyl-trimethylsilylpyrrolidinium bis(trifluoromethylsulfonyl)imide, N-methyl-trimethylsilylpyrrolidinium hexafluorophosphate. In addition, the additive is present in a range of 0.01 wt % to 10 wt %.
[0044] In one embodiment, the electrochemical energy storage device is a lithium secondary battery. In some embodiments, the secondary battery is a lithium battery, a lithium ion battery, a lithium sulfur battery, a lithium air battery, a sodium ion battery or a magnesium battery. In some embodiments, the electrochemical energy storage device is an electrochemical battery, such as a capacitor. In some embodiments, the capacitor is an asymmetric capacitor or a supercapacitor. In some embodiments, the electrochemical battery is a primary battery. In some embodiments, the primary battery is a lithium / MnO2 battery or a Li / poly (monocarbon fluoride) battery.
[0045] In an embodiment, a secondary battery is provided, the secondary battery including a positive electrode and a negative electrode separated from each other using a porous separator, and the electrolyte described herein.
[0046] Suitable cathode materials for secondary batteries containing the electrolytes described herein include those materials such as, but not limited to, vanadium oxide, lithium peroxide, sulfur, polysulfides, lithium carbon monofluoride (also known as LiCF x ) or a mixture of any two or more thereof, a carbon-coated olivine cathode (such as LiFePO4), a lithium metal oxide (such as LiCoO2, LiNiO2, LiNi x Co y Met z O2、LiMn 0.5 Ni 0.5 O2、LiMn 0.1 Co 0.1 Ni 0.8 O2、LiMn 0.2 Co 0.2 Ni 0.6 O2、LiMn 0.3 Co 0.2 Ni 0.5 O2、LiMn 0.33 Co 0.33 Ni 0.33 O2, LiMn2O4, LiFeO2, Li 1+x' Ni α Mn β Co γ Met' δ O 2-z' F z' ) or A n'B2(XO4)3, wherein Met is Al, Mg, Ti, B, Ga, Si, Mn, or Co; Met' is Mg, Zn, Al, Ga, B, Zr, or Ti; A is Li, Ag, Cu, Na, Mn, Fe, Co, Ni, Cu, or Zn; B is Ti, V, Cr, Fe, or Zr; X is P, S, Si, W, or Mo; and wherein 0≤x≤0.3, 0≤y≤0.5, 0≤z≤0.5, 0≤x'≤0.4, 0≤α≤1, 0≤β≤1, 0≤γ≤1, 0≤δ≤0.4, 0≤z'≤0.4, and 0≤n'≤3. In other embodiments, the formula of the olivine cathode is Li 1+x Fe 1z Met y PO 4-m X' n , wherein Met" is Al, Mg, Ti, B, Ga, Si, Ni, Mn or Co; X' is S or F; and wherein 0≤x≤0.3, 0 0≤y≤0.5, 0≤z≤0.5, 0≤m≤0.5 and 0≤n≤0.5.
[0047] Suitable anodes include materials such as lithium metal, graphite materials, amorphous carbon, carbon nanotubes, Li4Ti5O 12 , tin alloy, silicon, silicon alloy, intermetallic compound or any mixture of two or more such materials. Suitable graphite materials include natural graphite, artificial graphite, graphitized mesophase carbon microspheres (MCMB) and graphite fibers, and any amorphous carbon materials. In some embodiments, the anode electrode and the cathode electrode are separated from each other by a porous diaphragm.
[0048] In some embodiments, the anode is a composite anode including an active material such as silicon and a silicon alloy and a conductive polymer coating around the active material. The active material may be in the form of silicon particles having a particle size between about 1 nm and about 100 μm. Other suitable active materials include, but are not limited to, hard carbon, graphite, tin, and germanium particles. The polymer coating material may be cyclized using a heat treatment at a temperature of 200° C. to 400° C., thereby converting the polymer into a ladder compound by crosslinking the polymer chain. Specific polymers that may be used include, but are not limited to, polyacrylonitrile (PAN), in which cyclization converts the nitrile bond (C≡N) into a double bond (C═N). The polymer material forms an elastic but strong film to allow controlled crushing / crushing of silicon particles within the polymer matrix. In addition, the PAN matrix also provides a path for lithium ion migration, thereby improving the conductivity of the composite anode. The resulting anode material can overcome the expansion and conductivity challenges of silicon-based anodes, such as by providing a binder that can prevent silicon particles from expanding and a conductive additive for providing a path for lithium ion migration. In some embodiments, the polymer is about 10% to 40% by weight of the anode composite material. Additional descriptions of these Si-PAN composite anodes are provided in US Pat. Nos. 10,573,884 and 10,707,481, both of which are incorporated herein by reference in their entirety.
[0049] The separator for lithium batteries is generally a microporous polymer film. Examples of polymers for forming the film include polypropylene, polyethylene, nylon, cellulose, nitrocellulose, polysulfone, polyacrylonitrile, polyvinylidene fluoride, polybutene, or copolymers or blends of any two or more such polymers. In some cases, the separator is an electron beam treated microporous polyolefin separator. The electron treatment can increase the deformation temperature of the separator, thereby increasing the thermal stability of the separator at high temperatures. Additionally or alternatively, the separator can be a shut-down separator. The shut-down separator can have a trigger temperature higher than about 130°C to allow the electrochemical cell to operate at a temperature of up to about 130°C.
[0050] The present disclosure will be further described with reference to the following specific examples. It should be understood that these examples are given by way of illustration and are not intended to limit the present disclosure or the claims that follow.
[0051] Example A - Synthesis of triethylene glycol-thiolane
[0052]
[0053] 1. Triethylene glycol and dichloromethane (DCM) (20 mL) were added to a 100 mL three-necked flask equipped with a magnetic stirring bar, a water-cooled condenser, a N2 inlet, and a thermocouple. Triethylamine was added via a pipette and an exotherm to 24° C. was observed. The mixture was cooled to 0° C. in an ice bath.
[0054] 2. While stirring at 0°C, thionyl chloride was slowly added dropwise via syringe. Maximum exotherm was observed to 15°C, and white solid ppt (triethylamine-HCl) formed rapidly. When the addition was complete, the ice bath was removed. The colorless mixture was slowly returned to room temperature and stirred for 1 hour.
[0055] 3. Deionized water (2 x 20 mL) was added and the mixture was poured into a separatory funnel. The organic phase was extracted into DCM, separated, dried over MgSO4, filtered and the solvent stripped by rotary evaporation to give an oil. The oil was pumped out under high vacuum. The oil was passed through a 0.45 mm GMF filter and dried in a vacuum oven (5 mbar, 60° C.). Yield: thick colorless oil, 2.5 g (99%).
[0056] FTIR: 2870, 1198, 873, 698cm -1
[0057] Example B - Synthesis of triethylene glycol phenyl phosphate
[0058]
[0059] 1. Triethylene glycol and DCM (10 mL) were added to a 40 mL vial equipped with a magnetic stir bar and a thermocouple. Triethylamine was added via pipette and no exotherm was observed.
[0060] 2. While stirring at room temperature, phenyl dichlorophosphate was slowly added dropwise via syringe. An exotherm to 42°C was observed, and white solid ppt (triethylamine-HCl) formed rapidly. The pale yellow mixture was slowly returned to room temperature and stirred for 1 hour.
[0061] 3. Add deionized water (2 x 10 mL) and pour the mixture into a separatory funnel. Extract the organic phase into DCM, separate, wash with 5% HCl (5 mL), separate, dry over MgSO4, and strip the solvent by rotary evaporation to give an oil. Crude yield: thick yellow oil, 1.6 g (>99%).
[0062] FTIR: 3459, 2970, 1735, 1364, 1219, 931, 525cm -1 .
[0063] Example C - Electrolyte for NMC622 / Gr battery
[0064] In a dry argon-filled glove box, the electrolyte formulation was prepared by combining all electrolyte components in a glass vial and stirring for 24 hours to ensure complete dissolution of the salts. The functionalized crown ether was added to a base electrolyte formulation comprising a 3:7 by weight mixture of ethylene carbonate ("EC") and ethyl methyl carbonate ("EMC") and 1 M lithium hexafluorophosphate ("LiPF6") dissolved therein as Li + Ion-conductive salts. Conventional additives such as vinylene carbonate ("VC") and fluoroethylene carbonate ("FEC"). Comparative Example 1 (CE1) as shown in Table A. Example 1 (EE1) uses representative example molecules according to the present disclosure. The electrolyte components and additives used are summarized in Table A.
[0065] Table A - Electrolyte formulations for NMC 622 / Gr batteries
[0066]
[0067] Example D-NMC 622 / Gr battery electrochemical data
[0068] The prepared electrolyte formulation was used as the electrolyte in 200mAh lithium-ion pouch cells containing lithium nickel manganese cobalt oxide (NMC622) cathode active material and graphite as the anode active material. In each cell, 0.9mL of the electrolyte formulation was added and allowed to soak in the cell for 1 hour. The cells were vacuum sealed and initially charged at 25°C for 10 hours and then soaked. The cells were then charged to 3.8V at a C / 25 rate and then degassed and then vacuum sealed. After degassing, the cells were charged and discharged twice at a C / 10 rate between 4.45 and 3.0V and the results are summarized in Table B. The dQ / dV curves are shown in Table B. Figure 1 This shows that the addition of the functionalized crown ether results in a reduction peak at 2.4 V during the initial charge of the cell. This additional reduction peak indicates that the resulting SEI has changed. AC-IR is the internal resistance measured at 1 kHz, and the reported discharge capacity is the capacity of the last discharge at a C / 10 rate. The cells with EE1 electrolyte have lower AC-IR values compared to CE1, which is a result of the additive in the electrolyte.
[0069] Table B - Initial Cell Data for NMC 622 / Gr Cells
[0070] Electrolytes First coulombic efficiency (%) Formation discharge capacity (mAh) AC-IR(mΩ) CE1 87.4 203.5 97.5 EE1 86.9 200.4 92.4
[0071] The battery was then charged and discharged two hundred times at 0.5C rate between 4.45 and 3.0 V at 25°C. Figure 2As can be seen in Table C, the discharge capacity retention of the cells with EE1 electrolyte is comparable to that of the cells with CE1, indicating that the functionalized crown ether additives can perform a similar function as blends of conventional commercial additives. The capacity retention values are summarized in Table C.
[0072] Table C - Capacity retention data for NMC 622 / Gr batteries
[0073] Electrolytes Capacity retention after 50 cycles (%) Capacity retention after 100 cycles (%) CE1 90.6 74.3 EE1 93.7 79.0
[0074] Example E - Electrolyte for NMC811 / SiO+Gr battery
[0075] In a dry argon-filled glove box, the formulation was prepared by combining all electrolyte components in a glass vial and stirring for 24 hours to ensure a completely uniform mixture. The individual components of the electrolyte formulation are EC, EMC, FEC, 1,3-propane sultone (PaS), ethylene sulfate (ESA), LiPF6, lithium difluorophosphate (LFO), lithium bis(oxalate)borate (LiBOB) and 1,3,6,9-tetraoxa-2-thiacycloundecane-2,2-dioxide (EFCE). The base formulation for all test formulations is 1M LiPF6 in EC / EMC 30 / 70 weight base solvent, with 1.0 wt% LFO, 1 wt% LiBOB, 5 wt% FEC, 0.5 wt% PaS, 0.5 wt% ESA. The embodiment uses a representative example molecule EFCE according to the present disclosure at a concentration of 1.0 wt% and is easily miscible in solution. The electrolyte components and additives used are summarized in Table D.
[0076] Table D - Electrolyte formulation for NMC 811 / SiO+Gr battery
[0077]
[0078] Example F-NMC 811 / SiO+Gr battery electrochemical data
[0079] The prepared electrolyte formulation was used as the electrolyte in 900mAh lithium-ion pouch cells containing lithium nickel manganese cobalt oxide (NMC811) cathode active material and graphite as the anode active material combined with silicon oxide in a ratio of 9 to 1. In each cell, 2.5mL of the electrolyte formulation was added and allowed to soak in the cell for 1 hour. The cells were vacuum sealed and initially charged at 25°C for 24 hours and then soaked. The cells were then charged to 4.2V at a C / 10 rate, discharged to 2.7V at a C / 10 rate, and then degassed and vacuum sealed. After degassing, the cells were charged and discharged twice at a C / 10 rate between 4.2 and 2.7V, and the results are summarized in Table E. The dQ / dV curves are shown in Table E. Figure 3 This is shown in , indicating that the addition of the functionalized crown ether results in a reduction shoulder at 2.8V during the initial charge of the cell. This additional reduction peak indicates that the resulting SEI has changed. The AC-IR is the internal resistance measured at 1kHz, and the reported discharge capacity is the capacity of the last discharge at a C / 10 rate. The direct current internal resistance (DCIR) is then collected by applying a 10 second 1C discharge pulse to the cell and measuring the voltage drop of the cell. The cell with the EE2 electrolyte has lower AC-IR and DCIR values compared to the CE2, which is a result of the functionalized crown ether in the electrolyte.
[0080] Table E - Initial Cell Data for NMC 811 / SiO+Gr Cells
[0081] Electrolytes Initial discharge capacity (mAh) DCIR(mΩ) AC-IR(mΩ) CE2 956.0 92.9 26.6 EE2 956.8 80.3 22.5
[0082] The battery was then charged and discharged at 1.0C rate between 4.2 and 2.7 V for two hundred cycles at 25°C. Figure 4 As can be seen in Table F, the discharge capacity retention of the cells with EE2 electrolyte is comparable to that of the cells with CE2, indicating that the functionalized crown ether additives can perform a similar function as blends of conventional commercial additives. The capacity retention values are summarized in Table F.
[0083] Table F - Capacity retention data for NMC 811 / SiO+Gr cells
[0084] Electrolytes Capacity retention after 50 cycles (%) Capacity retention after 200 cycles (%) CE2 90.0 80.0 EE2 90.4 81.1
[0085] Although various embodiments have been depicted and described in detail herein, those skilled in the relevant art will appreciate that various modifications, additions, substitutions, etc. may be made without departing from the spirit of the present disclosure, and therefore such modifications, additions, substitutions, etc. are considered to be within the scope of the present disclosure as defined in the appended claims.
Claims
1. An electrolyte for an electrochemical energy storage device, comprising: Aprotic organic solvents; Metal salts; and At least one compound according to formula I, II or III (I) (II) (III) in: n is an integer ranging from 2 to 8; X is independently oxygen or sulfur; and R is independently further bonded to C1-C 12 Substituted or unsubstituted alkyl group or C6-C 14 The halogen, oxygen or sulfur atom of the aryl group, C1-C 12 Substituted or unsubstituted alkyl group or C6-C 14 Aryl groups, wherein any hydrogen atom may be replaced by an epoxide, halogen, alkyl, alkoxy, perfluoroalkyl, silanyl, silanyloxy, silane, sulfoxide, amide, azo, ether and thioether group or a combination thereof, or the carbon atom may be unsubstituted or substituted by an epoxide, halogen, alkyl, alkoxy, perfluoroalkyl, silanyl, silanyloxy, silane, sulfoxide, amide, azo, ether and thioether group or a combination thereof.
2. The electrolyte of claim 1, wherein the at least one compound according to formula I, II or III is one of the following structures:
3. The electrolyte of claim 1, wherein the at least one compound according to formula I, II or III is present in a concentration of 0.01% to 10% by weight of the electrolyte.
4. The electrolyte of claim 1, wherein the aprotic organic solvent comprises an open chain or cyclic carbonate, carboxylate, nitrite, ether, sulfone, ketone, lactone, dioxolane, glycol dimethyl ether, crown ether, siloxane, phosphate, phosphite, monophosphazene or polyphosphazene or a mixture thereof. 5 . The electrolyte of claim 1 , wherein the aprotic organic solvent is present in a concentration of 50 to 90 wt % of the electrolyte. The electrolyte according to claim 1 , wherein the cation of the metal salt is an alkali metal.
7. The electrolyte according to claim 6, wherein the alkali metal is lithium or sodium.
8. The electrolyte of claim 1, wherein the metal salt is present in the electrolyte at a concentration of 10 wt% to 30 wt%.
9. The electrolyte of claim 1, further comprising at least one additive.
10. The electrolyte of claim 9, wherein the at least one additive comprises a sulfur-containing compound, a phosphorus-containing compound, a boron-containing compound, a silicon-containing compound, a fluorine-containing compound, a nitrogen-containing compound, a compound containing at least one unsaturated carbon-carbon bond, a carboxylic anhydride, an epoxide, or a mixture thereof.
11. The electrolyte of claim 10, wherein the at least one additive is present in the electrolyte at a concentration of 0.01 wt% to 10 wt%.
12. An electrochemical energy storage device comprising: cathode; anode; The electrolyte according to claim 1; and Diaphragm.
13. The device of claim 12, wherein the cathode comprises lithium metal oxide, spinel, olivine, carbon-coated olivine, vanadium oxide, lithium peroxide, sulfur, lithium polysulfide, lithium carbon monofluoride, or mixtures thereof.
14. The device of claim 13, wherein the lithium metal oxide is LiCoO2, LiNiO2, LiNi x Co y Met z O2、LiMn 0.5 Ni 0.5 O2、LiMn 0.1 Co 0.1 Ni 0.8 O2、LiMn 0.2 Co 0.2 Ni 0.6 O2、LiMn 0.3 Co 0.2 Ni 0.5 O2、LiMn 0.33 Co 0.33 Ni 0.33 O2, LiMn2O4, LiFeO2, Li 1+x' Ni α Mn β Co γ Met' δ O 2-z' F z' or A n' B2(XO4)3, wherein Met is Al, Mg, Ti, B, Ga, Si, Mn or Co; Met' is Mg, Zn, Al, Ga, B, Zr or Ti; A is Li, Ag, Cu, Na, Mn, Fe, Co, Ni, Cu or Zn; B is Ti, V, Cr, Fe or Zr; X is P, S, Si, W or Mo; and wherein 0≤x≤0.3, 0≤y≤0.5, 0≤z≤0.5, 0≤x'≤0.4, 0≤α≤1, 0≤β≤1, 0≤γ≤1, 0≤δ≤0.4, 0≤z'≤0.4 and 0≤h'≤3.
15. The device of claim 12, wherein the anode comprises lithium metal, graphite material, amorphous carbon, Li4Ti5O 12 , tin alloy, silicon, silicon alloy, intermetallic compound or mixture thereof.
16. The device of claim 15, wherein the anode is a composite anode comprising an active material silicon or a silicon alloy and a conductive polymer coating around the active material.
17. The device of claim 16, wherein the conductive polymer is polyacrylonitrile (PAN).
18. The device of claim 12, wherein the separator comprises a porous separator separating the anode and the cathode from each other.
19. The device of claim 18, wherein the porous membrane comprises an electron beam treated microporous polyolefin membrane or a microporous polymer membrane comprising nylon, cellulose, nitrocellulose, polysulfone, polyacrylonitrile, polyvinylidene fluoride, polypropylene, polyethylene, polybutylene, or a copolymer or blend of any two or more of such polymers.
20. The device of claim 12, wherein the aprotic organic solvent comprises an open chain or cyclic carbonate, carboxylate, nitrite, ether, sulfone, ketone, lactone, dioxolane, glyme, crown ether, siloxane, phosphate, phosphite, monophosphazene or polyphosphazene or a mixture thereof.
21. The device of claim 12, wherein the aprotic organic solvent is present in the electrolyte at a concentration of 50 wt% to 90 wt%.
22. The device of claim 12, wherein the cation of the metal salt is an alkali metal.
23. The device of claim 22, wherein the alkali metal is lithium or sodium.
24. The device of claim 12, wherein the metal salt is present in the electrolyte at a concentration of 10 wt% to 30 wt%.
25. The device of claim 12, wherein the electrolyte further comprises at least one additive.
26. The apparatus of claim 25, wherein the at least one additive comprises a sulfur-containing compound, a phosphorus-containing compound, a boron-containing compound, a silicon-containing compound, a fluorine-containing compound, a nitrogen-containing compound, a compound containing at least one unsaturated carbon-carbon bond, a carboxylic anhydride, an epoxide, or a mixture thereof.
27. The device of claim 25, wherein the at least one additive is present in the electrolyte at a concentration of 0.01 wt% to 10 wt%.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery
JP2000195548A
Ionic liquid-enabled high-energy Li-ion batteries
US10573884B2
Stable silicon-ionic liquid interface lithium-ion batteries
US10707481B2
Lithium ion battery
US9130231B2
Non-aqueous electrolyte for high-voltage lithium ion battery and lithium ion battery
CN112448034A
Cited By
Lithium metal battery electrolyte and lithium metal battery
CN120749234A